Antimicrobial resistance patterns of Acinetobacter baumannii colonization patients skin - Taha, Aza Bahadeen (Journal of the Faculty of Medicine Baghdad, 2020)
Background: Acinetobacter baumannii is a significant opportunistic pathogen and it is generally associated with benign colonization of hospitalized patients. Objective: To investigate skin colonizationwith Acinetobacter baumannii in hospitalized patients and healthy volunteers.Antimicrobial resistance patterns of Acinetobacter baumanniiwas assessed by determining the minimum inhibitory concentrations (MICs) of thirteen different antimicrobial agents. Patients and Methods: The study performed on hospitalized patients at Rizgary and Hawler teaching hospitals and healthy volunteers who attended to supermarkets in Erbil, Iraq. A single sample was obtained once from each of the forehead, one ear pinna, one armpit, finger webs of one hand and toe webs of one footto isolatedAcinetobacter baumannii,then identified using phenotypic and genotypic properties. All isolates examined for their antimicrobial susceptibility by the agar dilution method. Results: Among 600 hospitalized patients, 79 (13.17%) colonized with Acinetobacter baumannii, yielding 155 isolates that are resistant to 57.42% ceftriaxone, 56.77% cefotaxime, 45.81% ceftazidime and 40.65% ciprofloxacin.While the most effective antimicrobial agents with MIC50/90 values (minimum inhibitory concentrations required to inhibit 50% and 90% of the isolates, respectively) were as follows: imipenem, 80.65%, 0.25/16 mg/L; doxycycline, 80.65%, 1/16mg/L; amikacin, 79.35%, 2/64 mg/L. However, 53 Acinetobacter baumannii isolated from healthy volunteers that showedresistance to 50.94% ceftriaxone (MIC50/90, 64/128 mg/L), 45.28% ceftazidime, 43.40% cefotaxime, and 35.85% ciprofloxacin. Fortunately, all 208 Acinetobacter baumannii were sensitive to polymyxin B (MIC50=0.25mg/L). Conclusion: The rates of Acinetobacter baumannii colonizedpatients higher thanhealthy volunteers, whereas an antimicrobial minimum inhibitory concentrations value of cefepime, cefotaxime, imipenem, amikacin, ciprofloxacin, and levofloxacin were significantly higher in patients than healthy volunteers. Polymyxin B had activity against all Acinetobacter baumannii strains.